2021
DOI: 10.1093/neuonc/noab046
|View full text |Cite
|
Sign up to set email alerts
|

The combined use of steroids and immune checkpoint inhibitors in brain metastasis patients: a systematic review and meta-analysis

Abstract: Background Immune checkpoint inhibitors (ICI) have been a breakthrough for selected cancer patients, including those with brain metastases (BMs). Likewise, steroids have been an integral component of symptomatic management of BM patients. However, clinical evidence on the interaction between ICI and steroids in BM patients is conflicting and has not adequately been summarized thus far. Hence, the aim of this study was to perform a systematic literature review and meta-analysis on the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 52 publications
0
30
0
Order By: Relevance
“…As described in experimental models, steroids significantly reduce circulating T-cells and increase PD-1 expression, hampering anti-tumoral immune responses and ICIs' efficacy (56,57). Steroids showed a detrimental effect on the survival of patients with brain metastases undergoing ICI therapy (58,59). Brastianos et al (9) reported worse OS in patients with LMD receiving steroids concurrent to pembrolizumab (2.4 months) compared to the non-steroid group (5.1 months), but differences were not significant (p=0.32).…”
Section: Discussionmentioning
confidence: 94%
“…As described in experimental models, steroids significantly reduce circulating T-cells and increase PD-1 expression, hampering anti-tumoral immune responses and ICIs' efficacy (56,57). Steroids showed a detrimental effect on the survival of patients with brain metastases undergoing ICI therapy (58,59). Brastianos et al (9) reported worse OS in patients with LMD receiving steroids concurrent to pembrolizumab (2.4 months) compared to the non-steroid group (5.1 months), but differences were not significant (p=0.32).…”
Section: Discussionmentioning
confidence: 94%
“…Symptomatic BMs often have poor efficacy and outcome. Besides active BMs per se, the decline in the efficacy of immunotherapy is attributed to steroids, which are considered immune suppressors and routinely used to control intracranial symptoms and modify side effects of other therapies in patients with BMs ( 14 , 98 ). Moreover, harboring driver-gene mutation, indicating a favorable prognosis, is associated with low benefits from ICIs ( 99 ).…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…However, for those with unknown PD-L1 expression levels, the response rate was only 17%-19% ( 21 23 ). In addition, the results of previous clinical trials also showed that immunotherapy in combination with radiotherapy (RT) or CT might improve the survival of NSCLC patients ( 24 26 ).…”
Section: Introductionmentioning
confidence: 99%